Proyectos integrados de yuca: Una metodologia para el desarrollo rural - Pérez Crespo, C.A. (International Center for Tropical Agriculture, 1991)
Strategies that have been used for cassava development (market penetration, product development, market development, diversification, and integrated agroindustrial transformation) are described. The concept of the integrated cassava project is defined and its origins are discussed in the context of CIAT's cassava program as it strove to be more effective and responsive to farmers. This strategy implies the intervention in 2 different but complementary areas: technology and institutional strengthening. Although an integrated cassava program has many elements in common with integrated rural development programs, they differ in that an integrated cassava program concentrates its activities in a reduced geographic area and seeks narrower objectives; it can also be incorporated with integrated rural development. Secondly, an integrated cassava program requires public and private investment, but it is mainly a technology-induced development program. The element that releases development is the adoption of a technology. (CIAT)